Intensification strength in speech: language-specific preferences and differences between native and learner language - Hendrikx, Isa; Van Goethem, Kristel; Buntinx, Natacha (Dutch Journal of Applied Linguistics, 2024)
In this article we analyse the use of intensification in the spoken productions of French-speaking learners of Dutch and English. We compare the strength of intensifiers used by learners in their first language (L1) and in their additional language (AL), and contrast these results with data from control groups of L1 speakers. Our corpus results indicate that L1 English speakers tend to intensify more frequently but opt for weaker intensifiers, while L1 French speakers intensify less frequently but use stronger intensifiers. L1 Dutch speakers take the middle position in both aspects. The analysis of the learner corpora reveals overall more similarities between AL English and L1 English than between AL Dutch and L1 Dutch, confirming the trends observed in previous studies on the same learners (Hendrikx, 2019).